Acid-labile pHPMA modification of four-arm oligoaminoamide pDNA polyplexes balances shielding and gene transfer activity in vitro and in vivo - Beckert, Linda; Kostka, Libor; Kessel, Eva; Krhac Levacic, Ana; Kostkova, Hana; Etrych, Tomas; Lächelt, Ulrich; Wagner, Ernst (European journal of pharmaceutics and biopharmaceutics, 2016)
We report novel pH-reversibly surface-shielded polyplexes with enhanced gene transfer activity upon systemic administration. A four-arm-structured sequence-defined cationic oligomer KK[HK[(H-Sph-K)3HC]2]2 was designed and synthesized on solid-phase, containing additional lysine residues not only for improved pDNA polyplex stability, but also providing attachment points for subsequent polyplex functionalization with amine-reactive shielding polymers. Herein, the surface of polyplexes was shielded with hydrophilic polymers, monovalent PEG or monovalent and multivalent pHPMA, optionally attached to the polyplex via the acid-labile linker AzMMMan. Overall, surface modification with PEG or pHPMA resulted in a decrease in the zeta potential of polyplexes, consistent with the degree of surface shielding. At pH 6.0, only polyplexes modified via the acid-labile linkage showed an increase in zeta potential, consistent with a "deshielding" in acidic environment, expected as beneficial for endosomal escape. Shielding was more efficient for multivalent pHPMA (20kDa, 30kDa) as compared to monovalent pHPMA (10kDa, 20kDa, 30kDa) or PEG (5kDa). In vitro transfection studies revealed higher gene expression by the polyplexes with the acid-labile shield as compared to their irreversibly shielded counterparts. Intravenous administration of AzMMMan-pHPMA modified polyplexes in an in vivo tumor mouse model mediated enhanced gene expression in the subcutaneous tumor and reduced undesirable expression in the liver.
Keywords: Animals; Methacrylates; Gene Transfer Techniques; Amides; methakryláty; In Vitro Techniques; techniky in vitro; DNA; amidy; Mice; technika přenosu genů; myši; pHPMA; AzMMMan; zvířata; Plasmid DNA; Non-viral gene delivery; pH-sensitive shielding; PEG